1997
DOI: 10.1101/gad.11.7.863
|View full text |Cite
|
Sign up to set email alerts
|

UbcD1, a Drosophila ubiquitin-conjugating enzyme required for proper telomere behavior.

Abstract: The end-to-end association of chromosomes through their telomeres has been observed in normal cells of certain organisms, as well as in senescent and tumor cells. The molecular mechanisms underlying this phenomenon are currently unknown. We show here that five independent mutant alleles in the Drosophila UbcDl gene cause frequent telomere-telomere attachments during both mitosis and male meiosis that are not seen in wild type. These telomeric associations involve all the telomeres of the D. melanogaster chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 55 publications
11
84
0
Order By: Relevance
“…Since DTAs and STAs are thought to be generated during G 1 and S-G 2 , respectively (de Lange 2002), each type of TA was considered as a single fusion event (Table 1). Telomeric associations observed in nbs 1 mutants involved all chromosome ends (data not shown), as observed in rad50, mre11, UbcD1, Su(var)205, cav, and woc mutants (Cenci et al 1997(Cenci et al , 2003Fanti et al 1998;Ciapponi et al 2004;Raffa et al 2005). Surprisingly, the frequency of TAs observed in nbs 1 mutant brains is approximately one-half of that found in either rad50 D5.1 or mre11 DC null mutants (Table 1; Ciapponi et al 2004).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Since DTAs and STAs are thought to be generated during G 1 and S-G 2 , respectively (de Lange 2002), each type of TA was considered as a single fusion event (Table 1). Telomeric associations observed in nbs 1 mutants involved all chromosome ends (data not shown), as observed in rad50, mre11, UbcD1, Su(var)205, cav, and woc mutants (Cenci et al 1997(Cenci et al , 2003Fanti et al 1998;Ciapponi et al 2004;Raffa et al 2005). Surprisingly, the frequency of TAs observed in nbs 1 mutant brains is approximately one-half of that found in either rad50 D5.1 or mre11 DC null mutants (Table 1; Ciapponi et al 2004).…”
Section: Resultsmentioning
confidence: 82%
“…Chromosome cytology and analysis of telomeric fusions: DAPI-stained larval brain chromosome preparations were made as described previously (Cenci et al 1997). For each mutant or doubly mutant brain (Table 1), we examined between 40 and 60 metaphases for the presence of both TAs and chromosome breaks.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, telomeric associations have been reported as a consequence of mutations in the UbcD1 gene in Drosophila melanogaster (Cenci et al, 1997), as well as mutations in a telomerase template in Tetrahymena thermophila (Kirk et al, 1997). To determine whether ATM function in¯uences TA, we examined metaphase spreads and found that RKO cells expressing dominant-negative fragments exhibited a 3 ± 6-fold higher frequency of cells with TA compared to parental and control RKO cells (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in this gene cause high frequencies of telomeric fusions independent of the presence of HTT elements (46,47). It is not known whether the UbcD1 protein causes polyubiquitination and degradation of a telomere component or mono-ubiquitination resulting in modified allosteric conformation and activity of its substrate, nor is the substrate known.…”
Section: Proteins Associated With the Capmentioning
confidence: 99%